The accessibility and usage of smartphones by Arab-speaking visually impaired people. Issue 4 (2nd November 2015) - Al-Mouh, Najd; Al-Khalifa, Hend S.
Abstract : Purpose: – This paper aims to investigate accessibility and usage of mobile smartphones by Arabic-speaking visually impaired people in Saudi Arabia. Design/methodology/approach: – In total, 104 participants with visual impairments were interviewed about their use of mobile phones with the following questions: What is the most commonly used mobile phone? What is the popular domain for which they use mobile phones? What are their favorite applications? What accessibility challenges do they usually face while using mobile phones? How often do they use the Internet via mobile phones and what are the reasons behind that? Findings: – This research is the first study with such magnitude to investigate smartphone usage by Arabic-speaking visually impaired people. The survey has revealed that Arabic-speaking visually impaired people utilize mobile phones in different ways and strategies. Getting assistance in performing daily tasks and navigating independently are two of the most common uses for mobile phones. Originality/value: – Based on the findings, the authors are going to propose some guidelines to developers to improve smartphone accessibility, application design and Internet usage to improve accessibility for visually impaired people.